Peningkatan Kompetensi Guru-Guru IPA SMP/MTsN Lubuk Sikaping melalui Pelatihan Pengembangan Bahan Ajar Berbasis Kontekstual - Hufri Hufri; Letmi Dwiridal; Silvi Yulia Sari (Universitas Mathla'ul Anwar Banten, 2021)
INCREASING THE COMPETENCE OF SCIENCE TEACHERS OF SMP/MTSN LUBUK SIKAPING THROUGH CONTEXTUAL-BASED LEARNING MATERIALS DEVELOPMENT TRAINING. This activity aims to improve the competence of science teachers SMP/MTsN Lubuk Sikaping through training development of contextual based teaching materials. To achieve the objectives and targets set, the method used consists of observation, orientation and discussion, preparation, implementation, monitoring and evaluation. The instruments used are tests of understanding of the material and questionnaire responses of trainees. Data analysis techniques used are paired t test and percentage analysis Based on data analysis, obtained the average value of pretest is 46.2676 and at postest 63.0672. Furthermore, paired t test, obtained results of significance 0.000 <0.05. This indicates that there is an increase in the competence of IPA teachers of SMP/MTsN Lubuk Sikaping through training of contextual based teaching materials. Based on the questionnaire given at the end of the training activities, that the activity is very useful and related to the subjects which is taught in schools.